VD_FINDINFO HC / 2024 / 888 vom 14. November 2024 - VD Tribunal cantonal (2024)
ATTRIBUTION DE L'EFFET SUSPENSIF, RELATIONS PERSONNELLES, INTÉRÊT DE L'ENFANT | 315 al. 4 let. b CPC (CH), 315 al. 5 CPC (CH)